Prohibition of Usury in the Perspective of Hadith and its Implementation in the Monetary System in Indonesia - idwal; Aan Supian (Sharia Economic and Management Business Journal (SEMBJ), 2023)
. The uncompromising emphasis of usury on socioeconomic justice and equitable distribution of income and wealth. From this it is very clear, that with the interest system, the distribution of money will not be evenly distributed, there is no justice, who can enjoy only those who have large capital, while those who are weak in terms of capital, will be downtrodden, out of business which in turn will increase the statistics of the poor. The Prophet in the hadith described above expressly prohibits eating usury, because it is included in the seven major sins that are cursed and destroyed by Allah SWT. Usury is Ziyadah or an addition to a loan that is already due. The practice of usury in the capitalist economic system is one of the sources of the economic crisis in this world. Indonesia recognizes the existence of dual banking systems in the monetary system, namely an interest-free Islamic banking system and a conventional banking system with an interest system.